Seeing Reality from a New Dimension - Jakob Hanschu (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2019)
Edwin A. Abbott’s book Flatland: A Romance of Many Dimensions presents the world of Flatland as a utopia from which the reader can gain an enhanced perspective on their constructed reality. Because all humans are restricted by what is known, assumed, and perceived, fiction literature peels away some of these restrictions by exercising peoples’ imaginations. When we think “outside the box,” as we often must do to wrap our minds around fiction works, we are presented the chance to realize that our perceptions are limited by our reality, and that our realized reality is limited by our perceptions. Flatland encourages this by recounting the fantastical journey of A Square from his limited world of two dimensions to Spaceland. The novel stretches the imagination while also making the reader aware that what they perceive as “real” is entirely dependent upon the “dimension” (i.e., socially, culturally, and historically constructed reality) in which they are situated. When we gain new perspectives, we arrive closer to truths about our world, and truths about ourselves. To do so, we must escape our own “flatlands.”
Keywords: Anthropology; utopia; ideology; dimensionality